English grammar in use 1999 - Murphy, Raymond (New York Cambridge university press, 1999)
"Using clear examples and easy-to-follow exercises, this new, full-colour edition of the best-selling 'Essential grammar in use' makes learning easy, covering all the areas of grammar that an elementary-level student needs."--Back cover.
Keywords: English language -- Grammar; English language -- Grammar -- Problems, exercises, etc; English language -- Textbooks for foreign speakers; Enseignement des langues